PELATIHAN PEMBUATAN GOOGLE EDU UNTUK PENILAIAN KURIKULUM MERDEKA DI SATUAN PAUD KABUPATEN TANAH DATAR - Jhoni Warmansyah; Restu Yunungsih; Meliana Sari; Abdul Halif; Saobil Sobri Solin; Roza Novita Sari (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
The Joint Community Service aimed to provide training for early childhood education (PAUD) teachers in utilizing Google for Education for assessing the "Kurikulum Merdeka" curriculum within Early Childhood Education Units. The Participatory Action Research (PAR) method was employed, involving 40 PAUD teachers from the Tanah Datar District. The outcomes of this training program can be summarized as follows: 1) A significant enhancement was observed in the teachers' comprehension and skills in leveraging the Google for Education platform for curriculum assessment within the framework of "Kurikulum Merdeka" in Early Childhood Education Units, and 2) the training program achieved an average rating of 3.92, indicating its effectiveness. The implications of this program are substantial, as it lays a strong foundation for schools to continue training PAUD teachers in utilizing educational technology, such as Google for Education, to support the "Kurikulum Merdeka." Furthermore, the utilization of the Participatory Action Research approach in this community engagement initiative can serve as a model for similar endeavors in other regions, promoting active involvement from all stakeholders in educational program planning and evaluation.